14. Resting sympathetic and cardiovascular activities during wake in narcolepsy with cataplexy. Issue 1 (January 2015) - Donadio, V.; Liguori, R.; Vandi, S.; Pizza, F.; Dauvilliers, Y.; Giannoccaro, M.P.; Leta, V.; Baruzzi, A.; Plazzi, G.
<x xml:space="preserve">Abstract</x> Conflicting data have been reported on resting autonomic tone in narcolepsy with cataplexy (NC) including both reduced or increased sympathetic activity. To settle this important point we measured muscle nerve sympathetic activity (MSNA) and cardiovascular activities in NC patients during wakefulness. We studied 19 NC untreated patients and 19 sex-age matched controls. Subjects underwent resting microneurographic recording of MSNA from peroneal nerve and heart rate (HR) whereas blood pressure (BP) was measured with a sphygmomanometer after the end of microneurographic recording. The awake state was continuously monitored by an ambulatory polygraphic recorder. NC patients displayed significantly lower resting MSNA, HR and BP values than controls. Pearson regression analysis showed a significant correlation between CSF hypocretin-1 level and MSNA or HR whereas no correlation was found with BP; however patients with virtually absent hypocretin-1 displayed lower BP than patients with the highest hypocretin-1 value. (1) NC patients displayed decreased resting MSNA, HR and BP during wakefulness lowering their cardiovascular risk profile; (2) a positive correlation supported a direct effect of CSF hypocretin-1 deficiency on MSNA or HR regulation; (3) although hypocretin-1 was not correlated with BP, patients with absent hypocretin-1 had lower BP.